theoretical approach of leisure, free time and voice from the social actors (Revista Electrónica REDINE, 2018)
The intent of this research is to generate a theoretical approach of leisure time from the voice of social actors who are recreation specialists Lara state. To achieve this intent was unveiled the meaning assigned recreation specialists working in different levels of the Venezuelan education the concept of leisure and free time as a means of socializing individuals during educational activities. This qualitative approach is assumed, conceived under the interpretive paradigm with support hermeneutic phenomenological methods because it is aimed to know, understand and interpret the existing reality. Was applied unstructured interview to understand the meanings of events depends on the context of the actors in the research, after analyzing the evidence, information was categorized, and triangulated to finally generate the approximation.
Keywords: theoretical approach; leisure; free time